(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article provides an in-depth analysis of the methods for assessing the effectiveness of using the Duolingo mobile application in the process of teaching Arabic. In particular, in the development of digital technologies, the features of educational applications based on gamification and interactive, interesting approaches to the development of students’ language skills are highlighted. In addition, the learning outcomes, motivation, and activity of students using the Duolingo application and traditional teaching methods are compared using tests and data obtained from practical experience. This article contributes to enriching innovative strategies in Arabic language pedagogy and offers teachers scientifically based recommendations for more effective integration of technologies.